Time Preferences over the Life Cycle and Household Saving Puzzles - Wataru Kureishi; Hannah Paule-Paludkiewicz; Hitoshi Tsujiyama; Midori Wakabayashi (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Most economic models assume that time preferences are stable over time, but the evidence on their long-term stability is lacking. We study whether and how time preferences change over the life cycle, exploiting representative long-term panel data. We provide new evidence that discount rates decrease with age and the decline is remarkably linear over the life cycle. Decreasing discounting helps a canonical life-cycle model to explain the household saving puzzles of undersaving when young and oversaving after retirement. Relative to the model with constant discounting, the model's fit to consumption and asset data profiles improves by 40% and 30%, respectively.
Keywords: D15; D91; E21; J10; 330; time preferences; preference stability; discount rates; household saving puzzles